2021
DOI: 10.1111/cas.14801
|View full text |Cite|
|
Sign up to set email alerts
|

VEGFR2 blockade augments the effects of tyrosine kinase inhibitors by inhibiting angiogenesis and oncogenic signaling in oncogene‐driven non‐small‐cell lung cancers

Abstract: Molecular agents targeting the epidermal growth factor receptor (EGFR)‐, anaplastic lymphoma kinase (ALK)‐ or c‐ros oncogene 1 (ROS1) alterations have revolutionized the treatment of oncogene‐driven non‐small‐cell lung cancer (NSCLC). However, the emergence of acquired resistance remains a significant challenge, limiting the wider clinical success of these molecular targeted therapies. In this study, we investigated the efficacy of various molecular targeted agents, including erlotinib, alectinib, and crizotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Therefore, these results indicated that apatinib inhibited the growth of NSCLC cells through cell cycle arrest and apoptosis. Many studies have reported that A549 cells expressed a relative low level of VEGFR2 among NSCLC cell lines [36][37][38]. Our results presented evidence that NSCLC cells expressing low levels of VEGFR2 still responded to apatinib.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, these results indicated that apatinib inhibited the growth of NSCLC cells through cell cycle arrest and apoptosis. Many studies have reported that A549 cells expressed a relative low level of VEGFR2 among NSCLC cell lines [36][37][38]. Our results presented evidence that NSCLC cells expressing low levels of VEGFR2 still responded to apatinib.…”
Section: Discussionsupporting
confidence: 66%
“…Preclinical researches and clinical trials have demonstrated that anti-angiogenic drugs combined with EGFR-TKIs is a viable strategy for EGFR -mutant NSCLC patients [ 33 – 36 ]. According to the results of an ongoing phase II clinical trial, impressive objective response rate and disease control rate were obtained with acceptable toxicity after the united medication [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-angiogenic agents could also play a role in combination with a TKI. Combining vascular endothelial growth factor (VEGF)-pathway blockade with a TKI targeting ROS-1 in vitro improved the anti-tumor effect compared to TKI alone [ 113 ]. According to a study based on 14 patients, the crizotinib–bevacizumab combination achieved efficacy against ALK-positive, ROS-1-positive or MET-amplified tumors with 58.3% ORR and an acceptable tolerance profile.…”
Section: Treatment Of Ros-1-positive Nsclcsmentioning
confidence: 99%